2009
DOI: 10.1212/01.wnl.0000341272.48617.b0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical indicators of vitamin B 12 and folate insufficiency and cognitive decline

Abstract: Background:In some prospective studies, associations of serum vitamin B 12 and homocysteine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 42 publications
5
77
1
1
Order By: Relevance
“…Thus, some of the inconsistent findings across studies of B-vitamin effects on cognitive decline and dementia may be due to the range of nutrient status in the study population. Of ten cohort studies that examined the relations of these B-vitamins and cognitive decline, four reported protective associations with folate (164)(165)(166)(167) and three reported protective associations with vitamin B 12 (165,(168)(169)(170) but many found no association with one or the other Bvitamin (165,(170)(171)(172)(173)(174) . The Chicago Health and Ageing Project study found a deleterious effect of faster decline among persons with food and/or supplement intakes exceeding 400 mg/d (6) .…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 99%
“…Thus, some of the inconsistent findings across studies of B-vitamin effects on cognitive decline and dementia may be due to the range of nutrient status in the study population. Of ten cohort studies that examined the relations of these B-vitamins and cognitive decline, four reported protective associations with folate (164)(165)(166)(167) and three reported protective associations with vitamin B 12 (165,(168)(169)(170) but many found no association with one or the other Bvitamin (165,(170)(171)(172)(173)(174) . The Chicago Health and Ageing Project study found a deleterious effect of faster decline among persons with food and/or supplement intakes exceeding 400 mg/d (6) .…”
Section: B-vitamins Cognitive Decline and Alzheimer's Diseasementioning
confidence: 99%
“…A higher educational level and higher engagement in physical, cognitive and social activities are lifestyle factors that may reduce the risk of dementia or cognitive decline (Hamer and Chida 2009;Kareholt et al 2011;Morgan et al 2012;Niti et al 2008;Sattler et al 2012). Nutritional epidemiology has examined the potential benefit on cognition of fatty acids (van Gelder et al 2007), vitamins (Mangialasche et al 2010;Tangney et al 2009), fish (van Gelder et al 2007), fruit and vegetables (Hughes et al 2010) with favorable but not fully consistent results. Thus, both genetic and lifestyle-related factors are involved in cognitive decline and dementia, but these factors do not contribute independently to neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid deficiencies lead the development depression and slow down the response to antidepressant medication [23,24]. In some cases the first clinical manifestation of vitamin B12 deficiency is a psychiatric disorder and relatively common in old age in which mostly associated with cognitive impairments [25][26][27].…”
Section: Effect Of Micronutrient On Depressionmentioning
confidence: 99%